Expressão de miRNAs relacionados com a proliferação de precursores neuronais durante desenvolvimento cerebelar - Nakamura, Thabatta Karollynne Estevam [UNIFESP] (2019)
The cerebellum is an important organ to study development in the central nervous system. When matured, the cerebellum presents a well-defined three-layered cortex. Its development initiates during the embryonic period and ends post-natally. The cerebellar granular cells precursors (GCP), that give origin to the most abundant neurons in the cerebellum, have their maturation during the post-natal development. GCP proliferation is induced by the morphogenic factor sonic hedgehog (SHH), which is produced and secreted by the Purkinje cells. SHH signalling pathway activation leads to the transcription of target genes such as the GLI family and MYCN. Overexpression of these factors has been related to medulloblastoma development, a cerebellar tumor that mainly affects children. MicroRNAs (miRNAs) have been frequently related to the regulation of several cellular processes, including proliferation, differentiation and tumor development. Nonetheless, little has been studied about reactive oxygen species (ROS)-induced GCP proliferation, as well as miRNAs expression during the GCP proliferative stage. Our laboratory described a mutant mouse, which presents increases in ROS production as consequence of a Nox3 mutation, named Nox3eqlb. This murine lineage exhibits ataxia; abnormal cerebellar cytoarchitecture caused by an excessive GCP proliferation and disorganized Purkinje cells with underdeveloped dendritic trees. Thus, this project aimed to analyze miRNAs expression predicted to regulate SHH signaling factors during proliferation induced by ROS in GCP. Using bioinformatics strategies to select miRNAs and qPCR to quantify their expression in GCP, we suggested that ROS produced by the NADPH oxidase complex regulate miRNA biogenesis. Mice Nox3eqlb show similar miRNA profile expression during GCP development while we observed variations in miRNAs profile expression on the wild-type mice BALB/c. Furthermore, inhibition of ROS production by NOX through apocynin treatment shows reduction of miRNAs expression timedependent. Thus, we conclude that in GCP, miRNA predicted to regulate SHH signalling factors biogenesis, seems to be related to NOX activity, but how SHH, miRNA and NOX connects is still unclear. Further studies should be done to understand this mechanism of regulation.